A comparison of topical acyclovir with steroids in the treatment of herpes zoster keratouveitis. Issue 11 (November 1983) - McGill, J; Chapman, C
Abstract : Topical acyclovir has been compared with topical steroids in a coded controlled trial of the treatment of keratouveitis caused by herpes zoster in 40 patients. Topical acyclovir was significantly superior to topical steroids in terms of treatment duration (75 days to 280 days), with no recurrences after the patients were weaned off treatment; there was a 63% recurrence rate in the steroid group. Corneal epithelial disease resolved significantly quicker in the acyclovir treated group. If recurrences occurred in the steroid group, other parts of the eye not initially affected were also involved. Treatment of such recurrences was more difficult than treatment of the initial attack.